Investigating the potential use of existing buildings for vertical farming - Buchner, Lafras (Department of Construction Economics and Management, 2023)
There are numerous reasons for the implementation of Vertical Farming (VF). Some of these include the reducing quality of natural land, the less water consumed in the production process, the ability to control and monitor the growing environment and the plant's nutrients. This research aims to investigate whether or not existing buildings can be used to accommodate urban vertical farms. The objectives were focused on reviewing existing legislation, building design considerations, the possible usage of VF as a solution to urban decay, reviewing the global VF trends, and considering why real estate developers will not be interested in VF buildings. A qualitative approach was followed to create more referable knowledge in the VF field as, currently, there is not an abundance of academic sources available. Semi-structured interviews were held with five key stakeholders. The study was restricted to brick and mortar buildings, while little attention was paid to plant production. The study was limited to the Cape Town Metropole. This study only considered commercial-scale food production. The researcher was not interested in the performance of the individual buildings but is rather interested in the built environment as a whole. The findings suggest that, currently, it is only financially feasible to grow specialised products under controlled environments. Acknowledging that, possibly opens opportunities for new products to be explored and grown indoors. The practical implications of this research translate to legislation that needs to be updated and technological developments that are required to make the implementation of vertical farming affordable for everyday food production. In the meantime, more specialised crops are expected to be grown under vertical farming conditions. Future research can build on this study and should consider investigating the price correlation between the cost of land within cities where existing, vertical production areas can be found and the price of land in rural areas, where traditional farmland is located. The additional vertical production area gained in vertical farms should form part of the cost comparison between traditional farming land and VFs.